Derivational Affixes Used in Selected Song Lyrics of Westlife - I G B Wahyu Nugraha Putra; I Komang Sulatra; Agatha, Windy Priccillia (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This research discusses about affixes in selected song lyrics of Westlife. The researcher analysed twenty song’s lyrics of Westlife which is used as data source. Descriptive qualitative method was used in this research. The purpose of this research is to identify the derivational affixes found in selected song lyrics of Westlife. The result of this research shows 78 data of derivational affixes were found in selected song lyrics of Westlife. They were categorized into prefix and suffix. Prefix category found from the data source are prefix im-and mis-. Meanwhile, suffixes found are –ly, -ize, -ship, -ish, -ion, -ness, -less, -ful, -ous, -ence, -ing, and -en. All affixes found are classified into derivational prefix are im-, and mis- and derivational suffixes are –ly, -ize, -ship, -ish, -ion, -ness, -less, -ful, -ous, -ence, -ing, and -en. Those affixes give explanation about forming new word and new meaning in Westlife selected song’s lyrics.